Upper Blepharoplasty for Areola Reconstruction - Friedrich, O. L.; Heil, J.; Golatta, M.; Domschke, C.; Sohn, C.; Blumenstein, M. (Geburtshilfe und Frauenheilkunde, 2013)
Blepharoplasty is one of the most common rejuvenating facial plastic surgery procedures. The procedure has been described many times and has very few complications. The tissue removed from the upper eyelid during blepharoplasty can be used as a skin graft for areola reconstruction due to the tissueʼs similarity to the areolaʼs natural skin. The present study investigated the use of upper blepharoplasty for areola reconstruction. Criteria were patient satisfaction, objective measurements and the assessment of cosmesis by a panel of physicians. All eight patients included in the study were very satisfied with the cosmetic result. Objective measurements and assessment by a panel of physicians using photographs of the reconstructed nipple-areola complex showed very good aesthetic results.
Keywords: areola reconstruction; upper blepharoplasty; patient satisfaction